Costunolide prevents renal ischemia-reperfusion injury in rats by reducing autophagy, apoptosis, inflammation, and DNA damage - Mustafa Güler; Erol Akpinar; Ayhan Tanyeli; Selim Çomakli; Yasin Bayir (Iranian Journal of Basic Medical Sciences, 2023)
Objective(s): Renal ischemia-reperfusion (I/R) is a vital health condition leading to acute kidney injury. Costunolide (COST) is an actively used molecule clinically for its anti-inflammatory, antioxidant, and immunomodulatory properties. In the present study, we searched for the possible protective effects of COST against renal ischemia/reperfusion (I/R) injury in rats.Materials and Methods: We established a renal I/R rat model. We divided forty rats into four groups: group I (sham), group II (I/R), group III (I/R+COST 5 mg/kg), and group IV (I/R+COST 10 mg/kg). We collected blood, kidney, and lung samples for analysis. Results: COST administration performed anti-oxidant and anti-inflammatory activity by reducing oxidant parameters and proinflammatory cytokine levels. COST alleviated DNA damage through declining 8-hydroxydeoxyguanosine (8-OHdG) levels. In addition, COST diminished tubular damage and inflammation by reducing kidney injury molecule-1 (KIM-1) production. COST administration also ameliorated apoptosis and autophagy by decreasing caspase-3 and microtubule-associated protein light chain 3B (MAPLC3, LC3B) expression.Conclusion: COST demonstrated protective effects against renal I/R-induced injury.